Beaufort Formation (Late Tertiary) as Seen from Prince Patrick Island, Arctic Canada - Fyles, John G. (ARCTIC, 1990)
The Beaufort Formation, in its type area on Prince Patrick Island, is a single lithostratigraphic unit, a few tens of metres thick, consisting of unlithified sandy deposits of braided rivers. Organic beds in the sand have yielded more than 200 species of plants and insects and probably originated during the Pliocene, when the area supported coniferous forest. This Beaufort unit forms the thin eastern edge of a northwest-thickening wedge of sand and gravel beneath the western part of the island. These largely unexposed beds, up to several hundred metres thick, include the Beaufort unit and perhaps other older or younger deposits. On the islands northeast and southwest of Prince Patrick Island (Meighen Island to Banks Island), the name Beaufort Formation has been applied to similar deposits of late Tertiary age. Most recorded Beaufort beds on these islands are stratigraphically and paleontologically equivalent to the "type" Beaufort, but a few sites that have been called Beaufort (such as Duck Hawk Bluffs and the lower unit at Ballast Brook, on Banks Island) differ stratigraphically and paleontologically from the "type" Beaufort. This paper recommends that these deposits (probably middle Miocene) and others like them be assigned new stratigraphic names and not be included in the Beaufort Formation as now defined. Informal names Mary Sachs gravel (Duck Hawk Bluffs) and Ballast Brook beds are proposed as an initial step. Formal use of the name Beaufort Formation should be restricted to the western Arctic Islands.